Photocatalytic Degradation of Aqueous Ionic Liquid - Wan Ameri, Wan Amirah (Universiti Teknologi PETRONAS, 2016)
Ionic Liquid (IL) is a salt containing large cation and anion with low melting points which is below than 1000C.One of the ILs is 1-butyl-3-methylmidazolium chloride (bmimCl) which was found in the wastewater of biomass plant. BmimCl has been used widely for degradation in dye, pulp mill waste not in photocatalytic degradation with Fe/TiO2. Photocatalysis is a substance that works as a catalyst when there is light exposure. In this research work, iron doped titanium dioxide (Fe/TiO2) is used as the photocatalyst to degrade bmimCl. IL has very unique properties such as non-volatile, low vapour pressure, high thermal stability and it is a very good solvent. However, those unique properties of IL might pose a threat to the environment as those properties cause IL very hard to degrade.